Store-and-forward teleneurology results in a large Brazilian city - Valéria Cristina Scavasine; Michelle Zonkowski Ribas; Gabriella Augustin; Viviane de Hiroki Flumignan Zetola; Renata Dal-Prá Ducci; Marcos Christiano Lange (Arquivos de Neuro-Psiquiatria, 2022)
Background Neurology is a high-demand specialty with long waiting lines. Some pathologies require rapid decision-making. Through technology, telemedicine can allow neurological patients to have faster access to specialized assessment. In store-and-forward telemedicine, the specialist physician evaluates data collected by a general practitioner and optimizes screening.